Role of Inflammation in Endophthalmitis - J. L. Vallejo-Garcia; M. Asencio-Duran; N. Pastora-Salvador; P. Vinciguerra; M. R. Romano (Hindawi Limited, 2012)
Inflammation originating from infection of the vitreous cavity is called endophthalmitis. Attention has been focused on the epidemiologic, microbiologic reports, and treatment options; unfortunately, the role of the host immune reaction in the visual function damage is still not well understood. Endophthalmitis occurs most frequently after cataract surgery. In this paper we review the published literature regarding inflammatory mediators and apoptosis during the course of endophthalmitis. Toll-like receptors, cytokines, high-mobility group box 1 proteins, aB-crystallin and apoptosis have been studied during clinical and experimental cases of endophthalmitis. Further understanding of the host-immune reaction to vitreous infection is essential for the development of new therapies. The use of intravitreal antibiotics and corticosteroids, vitrectomy and systemic antibiotics for the preservation of visual function is still discouraging.